Antimicrobial Activity of Soil Borne Microbes against Pathogenic Bacterial Strain - Shaheer Khan, Umar Khalid, Haris Khan, Mehboob Ul Haq, Afnan Shafqat, Saira Bano, Khansaa Abid, Mohammed Tauqir, Iqbal Nisa9, Sabir Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Soil is a rich source of microbes including those that have the ability to impede the growth of pathogenic bacteria. Objective: The current study was designed to explore the antimicrobial activity of soil borne microbes against pathogenic bacterial strain. Methodology: This study was conducted in the microbiology laboratory of University of Swabi. The antimicrobial potential of soils was evaluated against five pathogenic strains (Pseudomonas, Staphylococcus aureus, Salmonella, Citrobacter and E.coli) using well diffusion assay. Antimicrobial activity of soils was assessed from the zone of inhibition around the wells. Results: Among the pathogenic strains, Citrobacter proved relatively more susceptible towards soils of both lawns in concentration dependent manner. Pseudomonas was susceptible towards the soil of Pharmacy lawn but did not respond to soil of Microbiology Lawn. Growth of other bacterial strains was not hampered by soil of any lawn. Conclusion: Based on current findings it is inferred that soils of both lawns are rich in microbes that produce secondary metabolites capable of inhibiting growth pathogenic strains. Keywords: Antimicrobial Activity; Soil Borne Microbes; Pathogenic Bacteria